Recent advances in coupled cluster computations of open-shell atomic nuclei - Marino Francesco; Bonaiti Francesca; Bacca Sonia; Demol Pepijn; Duguet Thomas; Hagen Gaute; Jansen Gustav; Tichai Alexander (EPJ Web of Conferences)
In this contribution, we report on recent progress in coupled-cluster simulations of open-shell atomic nuclei using interactions consistently derived from chiral effective field theory. In particular, we compare different coupled-cluster approaches by computing binding energies and electric dipole polarizabilities in medium-mass calcium isotopes.